Long-term Complications and Testicular Adrenal Rest Tumors in Congenital Adrenal Hyperplasia - Aylin Kılınç Uğurlu; Elif Özsu; Zehra Aycan (JCRPE)
Congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency accounts for approximately 95% of all CAH cases and is one of the most common inborn errors of metabolism. While glucocorticoid therapy has significantly improved patient outcomes, the focus has shifted towards managing the long-term effects. Numerous adverse outcomes have been associated with CAH, including those resulting from supraphysiological doses of glucocorticoid and mineralocorticoid replacement, excessive adrenal androgen secretion, and elevated levels of steroid precursors and adrenocorticotropic hormone. Despite advances in treatment, long-term complications persist due to the inability to replicate physiological hormone secretion fully. In this review, we explore critical aspects of managing CAH, focusing on cardiometabolic health, bone integrity, fertility, and other significant long-term consequences, informed by the latest literature.